Research framework for food security and sustainability - Effie Papargyropoulou; John Ingram; Guy M. Poppy; Tom Quested; Clara Valente; Lee Ann Jackson; Tim Hogg; Thom Achterbosch; Emanuele Paolo Sicuro; Susanne Bryngelsson; Isabelle Guelinckx; Peter Van Dael; et al. (npj Science of Food)
Abstract This article presents a framework for food security and sustainability research, developed by industry, academia, and public sector experts. Key priorities for collaborative research include reassessing food system contexts and drivers, adapting food system activities, transforming food system outcomes, developing and applying food system methodologies, and adopting an ethical and just lens. The framework emphasises the need for coordinated action across multiple scales and sectors, focusing on synergies and trade-offs as opposed to isolated food activities, to address complex challenges in food security and sustainability.